2008
DOI: 10.1002/jnr.21927
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic obstructive hydrocephalus in Aqp4 null mice

Abstract: Aquaporin-4 (Aqp4) is a water transport protein expressed in glia and ependymocytes in brain. We report here the unexpected occurrence of severe obstructive hydrocephalus in a random subset of Aqp4 knockout mice. Of 612 Aqp4 knockout mice produced by heterozygote–heterozygote or knockout–knockout breedings, 9.6% of offspring manifested progressive encephalomegaly. Encephalomegaly was never seen in wild-type or Aqp4 heterozygous mice. Examination of the subset encephalomegalic mice revealed marked triventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…Reports conflict as to whether AQP4 modulates BBB integrity (Feng et al, 2009;Saadoun et al, 2009;Zhou et al, 2008). Our electron microscopic analysis confirmed the presence of pericytes and endothelial tight junctions in Aqp4 mutant mice, and immunoblots revealed comparable levels of the tight junction proteins claudin-5, occludin and ZO-1 in the two genotypes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Reports conflict as to whether AQP4 modulates BBB integrity (Feng et al, 2009;Saadoun et al, 2009;Zhou et al, 2008). Our electron microscopic analysis confirmed the presence of pericytes and endothelial tight junctions in Aqp4 mutant mice, and immunoblots revealed comparable levels of the tight junction proteins claudin-5, occludin and ZO-1 in the two genotypes.…”
Section: Discussionsupporting
confidence: 84%
“…Our results were obtained in C57BL/6J mice and are in agreement with those obtained in CD1 mice by Saadoun et al (2009), but contrast those of Zhou et al (2008), also using CD1 mice. Notably, the former group failed to replicate BBB dysfunction in the mouse strain used by Zhou et al (Feng et al, 2009). Moreover, BBB permeability was found to be normal in a-syn 2/2 mice (Zeynalov et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…116 Feng et al experimented with Aqp4-knockout mice, which produced a sporadic 9.6% rate of encephalomegaly (triventricular hydrocephalus with elevated intracranial pressure [ICP]) by the age of 6 weeks, linking AQP4 to the development of congenital hydrocephalus in mice. 34 Bloch et al found accelerated progression of kaolin-induced hydrocephalus in Aqp4-knockout mice when compared with controls, with a significantly higher lateral ventricle volume and ICP measurements as early as 3 days after injection, suggesting that the lack of AQP4 channels is related to the development of hydrocephalus.…”
Section: 81mentioning
confidence: 98%
“…6,24,25 Approximately 10% of AQP4 2/2 mice exhibit congenital hydrocephalus, and experimentally induced hydrocephalus is more severe in these animals compared with wild-type mice. 26,27 Because AQP4 facilitates brain water absorption in the cerebral microvasculature, inadequate expression of this protein may be a predisposing factor in hydrocephalus.…”
mentioning
confidence: 99%